Pengembangan Industri Rumah Tangga Keripik Singkong di Kota Mataram - Hernawati Hernawati; Elita Maydasari; Suburi Rahman; Novita Hayatunufus; Fakhruroza Fakhruroza (Abdimas Mandalika, 2026)
Abstract:  This activity aims to develop the cassava chips home industry through training and assistance in production technology for making chips from local resources, training and management assistance. This activity was carried out in the household industry in Mataram City. The problems faced were limited knowledge in processing cassava using technology, low management knowledge. Through a participatory approach, the activities carried out were training in cassava processing with more modern production techniques using technology, training and assistance in product diversification and digital-based marketing strategies. In addition, training and assistance in simple business management included digital cash recording and production cost calculations so that business actors had the ability to manage finances sustainably. The results of the activity showed an increase in partners' skills in producing cassava chips with various variants with more consistent taste quality and longer product durability. The resulting product also experienced an increase in production volume. The social media-based marketing that was introduced was proven to be able to expand market reach beyond the Mataram City area. Increased sales turnover and partners' awareness of the importance of innovation in small businesses are real achievements of this program. Thus, this community service activity contributes significantly to encouraging community economic independence through the development of home industries based on local potential.Abstrak: Kegiatan ini bertujuan untuk mengembangkan industri rumah tangga keripik singkong melalui pelatihan dan pendampingan teknologi produksi pembuatan keripik dari bahan baku lokal, pelatihan dan pendampingan manajemen. Kegiatan ini dilaksanakan pada industri rumah tangga di Kota Mataram. Permasalahan yang dihadapi adalah pengetahuan yang terbatas dalam pengolahan singkong menggunakan teknologi, dan pengetahuan manajemen yang rendah. Melalui pendekatan partisipatif, kegiatan yang dilakukan meliputi pelatihan pengolahan singkong dengan teknik produksi yang lebih modern menggunakan teknologi, pelatihan dan pendampingan diversifikasi produk dan strategi pemasaran berbasis digital. Selain itu, pelatihan dan pendampingan manajemen bisnis sederhana mencakup pencatatan kas digital dan perhitungan biaya produksi sehingga pelaku usaha memiliki kemampuan mengelola keuangan secara berkelanjutan. Hasil kegiatan menunjukkan peningkatan keterampilan mitra dalam memproduksi keripik singkong dengan berbagai varian dengan kualitas rasa yang lebih konsisten dan daya tahan produk yang lebih lama. Produk yang dihasilkan juga mengalami peningkatan volume produksi. Pemasaran berbasis media sosial yang diperkenalkan terbukti mampu memperluas jangkauan pasar di luar wilayah Kota Mataram. Peningkatan omset penjualan dan kesadaran mitra akan pentingnya inovasi dalam usaha kecil merupakan pencapaian nyata dari program ini. Dengan demikian, kegiatan pengabdian masyarakat ini memberikan kontribusi signifikan dalam mendorong kemandirian ekonomi masyarakat melalui pengembangan industri rumah tangga berbasis kearifan lokal